Empowerment of Karangtaruna in Polengan Village through Fish Cultivation and "Herbamina" Medicinal Plant - Lutfiyati, Heni; Yuliastuti, Fitriana; Nuryanto, Nuryanto (Journal of Community Services and Engagement, 2018)
Livelihoods of Polengan Village are 83% as sand miners. Village potential with abundant water has not been used optimally by the community, especially young people due to lack of knowledge about a good fish farming. Some families have used this abundant water by making a fish pond in the yard of the house but this pool is just for fun or hobbies and has not been commercialized. Looking at the phenomena,  it is necessary to empower youth to utilize the potential of this village to form a productive business unit focusing on fish cultivation by applying HERBAMINA technology (cultivation of medicinal plants and fish) in which it will improve the economy of the community and produce medicinal plants that can be used by the community. This service activity includes training in good fish farming methods, training in making herbamina and training in the utilization of herbal products. Approach method through face to face, mentoring and mentoring. The results of these community activities have increased the motivation of youth to utilize the potential of water sources for economic improvement, increased youth’s knowledge and skills on how to fish well and increased knowledge of the use of herbal plants. The resulting community service programs are ponds with herbamina technology (fish cultivation and medicinal plants).